2021
DOI: 10.21203/rs.3.rs-555534/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is edema zone volume associated with Ki-67 index in glioblastoma patients?

Abstract: Purpose: Despite all the progress with genetic mapping and multimodal treatment, the prognosis of GBM remains poor, with median overall survival (OS) of only 12 to 15 months. Several studies showed correlations between clinical features and prognosis, however the same don`t occurs with radiological features. The purpose of this study is to determine possible correlations between the volumetric analysis of glioblastoma compartments and the proliferation index represented by Ki-67. Methods: We performed a retros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article was previously posted to the research square preprint server on May 28, 2021 [15]. This study was approved by the Fundação Faculdade Regional de Medicina de São José do Rio Preto (FAMERP) ethics committee and was performed according to institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This article was previously posted to the research square preprint server on May 28, 2021 [15]. This study was approved by the Fundação Faculdade Regional de Medicina de São José do Rio Preto (FAMERP) ethics committee and was performed according to institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Caramanti et al, on the other hand, found a positive correlation between Ki67 indexes and peritumoral edema on FLAIR, but curiously, not as expected on the solid enhancing component, hypothesized to have the highest cellularity (40). This nding may suggest that in these cases, peritumoral signal abnormalities may be more related to microinvasion than vasogenic edema.…”
Section: Discussionmentioning
confidence: 95%